THE PROBLEM OF FORMATION CREATIVITY OF UNIVERSITY STUDENTS IN MODERN INNOVATIVE ENVIRONMENT - Хоменко-Семенова, Л. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article deals with the formation of creative abilities of university students that are part of their professional activities. Posted components of creativity, ways to implement creative approaches and levels of creativity. Factors forming creative abilities while studying at university. Proved that innovative technologies such as: brainstorming, case-study, quest and web-quest, social advertising and social networks greatly influence the formation of creative abilities of students while studying at university